2004
DOI: 10.1142/s0218863504001967
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced SHG in Polyelectrolyte Complexed Hemicyanine Dye Langmuir–blodgett Films

Abstract: Complexation of ionic amphiphiles at the air-water interface by polyelectrolytes in the subphase has a pronounced effect of stabilization and deaggregation on the amphiphiles. We have effectively utilized the latter in the case of a hemicyanine dye based amphiphile. The aggregation of these amphiphiles is influenced by the rate of equilibration of the Langmuir film and the introduction of polyelectrolytes in the subphase is found to be a convenient method to suppress the aggregation. Langmuir-Blodgett films ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
(18 reference statements)
1
12
0
Order By: Relevance
“…[4,8±12] However, slow equilibration after spreading on the water surface was found to result in LB films with reduced aggregation and improved SHG. [12,13] We have now observed that such a film, apparently in a metastable state, exhibits a pronounced decay of SHG in successive measurements involving laser irradiation. The traditional solution to the problem of aggregation has been to admix the NLOphore-based amphiphile with molecules like fatty acids; [11] such an approach, however, leads to the dilution of the active molecule in the two-dimensional lattice and possibly phase separation.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…[4,8±12] However, slow equilibration after spreading on the water surface was found to result in LB films with reduced aggregation and improved SHG. [12,13] We have now observed that such a film, apparently in a metastable state, exhibits a pronounced decay of SHG in successive measurements involving laser irradiation. The traditional solution to the problem of aggregation has been to admix the NLOphore-based amphiphile with molecules like fatty acids; [11] such an approach, however, leads to the dilution of the active molecule in the two-dimensional lattice and possibly phase separation.…”
mentioning
confidence: 71%
“…[5,11] Temporal instability of Langmuir films of a close derivative of ODEP + has been monitored through their electronic spectra, [6] which revealed the growth of a dimer absorption at~340 nm with concomitant reduction of the monomer absorption at 480 nm. We have shown [12,13] were formed with polyelectrolytes in the subphase. The absorption spectra of the current LB films recorded immediately after fabrication and after each SHG measurement are displayed in Figure 3.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The research efforts devoted to the design and synthesis of suitable materials and the subsequent preparation of ordered LB films are mainly driven by the possible application of such films in, e.g., heterogeneous catalysis, [13,14] chemical [10,15] and biological sensors, [16] electrical and optical thin-film devices, [17,18] and (nonlinear) optics. [19][20][21] By virtue of the electronic and optical properties associated with the metal center, transition-metal complexes form another class of interesting compounds for thin-film applications and molecular materials, showing distinct advantages compared to organic molecules. Metal complexes offer the possibility for reversible redox chemistry and, owing to the ambipolar nature of their structure (e.g., oxidation on the metal and reduction on the ligands), the interesting feature of an excited state, created by a charge recombination reaction (electro(chemi)luminescence).…”
mentioning
confidence: 99%
“…Figure 8 shows the formation of smooth films in presence of CMC. SHG of monolayer LB film of ODEP + /Br -is considerably reduced due to molecular aggregation effects which creates blue-shifted absorption near 360 nm in addition to the absorption due to monomeric ODEP + at 453 nm (Chandra et al 2004) (figure 9a). LB films formed in presence of PSS on the other hand, show no aggregation (figure 9b); the small absorption near 360 nm in this case is due to the polyelectrolyte.…”
Section: Polyelectrolyte Templated Langmuir-blodgett Films: Second Hamentioning
confidence: 99%